Adsorbent for removing trace carbon dioxide and fluorocarbon compounds in trifluoromethane and preparation method thereof
Patent Information
- Application Number
- CN202611267995.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明旨在解决现有技术中吸附剂不可再生、成本高及深度脱除能力不足的问题,提供一种用于去除三氟甲烷中痕量二氧化碳及氟碳化合物吸附剂及其制备方法
本发明吸附剂不仅可将三氟甲烷中CO2降至100ppb以下、氟碳化合物降至0.05ppm以下,且可通过惰性气体升温吹扫实现多次再生,再生后吸附容量衰减率低于5%,大幅降低了电子级三氟甲烷的生产成本与固废处理压力。具体表现在以下几点:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic special gas purification and adsorption materials technology, specifically to an adsorbent for removing trace amounts of carbon dioxide and fluorocarbons from trifluoromethane and its preparation method. Background Technology
[0002] Trifluoromethane (CHF3) is a critical plasma etching and cleaning gas in semiconductor manufacturing. With the advancement of chip manufacturing processes, the purity requirements for trifluoromethane are extremely high, typically requiring that the content of impurities such as carbon dioxide (CO2) and fluorocarbon compounds (such as CFC-13 and HCFC-22) be reduced to below 1 ppm.
[0003] Existing purification technologies mainly face the following bottlenecks: 1. High energy consumption of distillation: Since CO2 and HFC-23 have similar boiling points, distillation separation alone requires a very high number of trays and reflux ratio, resulting in huge energy consumption.
[0004] 2. Limitations of Adsorbents: Chinese patent CN114272893A discloses a silver-zinc modified activated carbon adsorbent. Although it can reduce impurities to a certain extent, it still has significant drawbacks: First, silver, as a precious metal, leads to high raw material costs; second, the silver and zinc components are prone to valence changes or loss during long-term operation, resulting in adsorbent deactivation and non-renewability, causing resource waste and environmental pressure after disposal; third, its adsorption of CO2 mainly relies on physical action, which is difficult to meet the requirements of deep removal of trace impurities (ppb level) from electronic-grade gases.
[0005] Therefore, developing a novel adsorbent that is low in cost, has excellent adsorption performance, and is recyclable is an urgent need in the field of electronic specialty gases. Summary of the Invention
[0006] This invention aims to solve the problems of non-renewable adsorbents, high costs, and insufficient deep removal capabilities in existing technologies, and provides an adsorbent for removing trace amounts of carbon dioxide and fluorocarbons from trifluoromethane and its preparation method.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane, characterized by comprising the following steps: (1) Carrier pretreatment: Hydrophobic coconut shell activated carbon is acid washed and deashed, and then dried; (2) Preparation of impregnation solution: Dissolve soluble copper salt and soluble cerium salt in deionized water, add complexing agent citric acid, stir and mix evenly to obtain copper-cerium composite impregnation solution; (3) Impregnation: The hydrophobic coconut shell activated carbon after carrier pretreatment is immersed in the copper-cerium composite impregnation solution, stirred and impregnated to allow the active components to fully enter the pores, and then dried after removal; (4) Reduction calcination: The dried material is placed in a hydrogen-containing mixed atmosphere and calcined to obtain the finished adsorbent. Calcination under a hydrogen / nitrogen mixed atmosphere reduces some copper ions to cuprous ions (Cu). + Cuprous ions have unfilled d orbitals, which can undergo strong π-feedback coordination with CO2 molecules, thereby significantly enhancing their chemisorption capacity.
[0008] Furthermore, in step (1), the hydrophobic coconut shell activated carbon has a particle size of 20-40 mesh and a specific surface area of 800-1200 m². 2 / g; The method for acid washing and deashing is as follows: boil in 0.5-1 mol / L dilute hydrochloric acid for 1-2 hours; The drying conditions are: 80-120℃ for 10-15 hours.
[0009] Furthermore, in step (2), the soluble copper salt is copper nitrate, the soluble cerium salt is cerium nitrate, the molar ratio of copper to cerium is 1:(0.5-2), and the total metal ion concentration in the impregnation solution is 3-10 wt%. Copper nitrate, cerium nitrate, and citric acid are mixed in a specific ratio to form a stable metal complex solution, preventing the hydrolysis and precipitation of metal ions.
[0010] Furthermore, in step (2), the amount of citric acid added is 10%-30% of the total mass of copper salt and cerium salt; The mixing time is 10-60 minutes.
[0011] Furthermore, in step (3), the volume ratio of the pretreated hydrophobic coconut shell activated carbon to the copper-cerium composite impregnation solution is 1:1-3. The stirring and soaking time is 20-50 minutes; The drying conditions are: 100-140℃ for 2-6 hours.
[0012] Furthermore, in step (4), the hydrogen-containing mixed atmosphere is a mixture of hydrogen and nitrogen, wherein the volume percentage of hydrogen is 5%-10%, and the heating rate during the calcination process is 3-5℃ / min.
[0013] Furthermore, in step (4), the roasting temperature is 350-500℃ and the time is 2-5h.
[0014] Furthermore, step (4) includes an activation step, in which the roasted material is purged with high-purity nitrogen at 200-300°C for 1-2 hours to remove residual acidic gases on the surface. The purity of the high-purity nitrogen is 5N grade.
[0015] An adsorbent prepared by the above method, the adsorbent comprising copper species on the surface of activated carbon and cerium species dispersed in the pores of activated carbon, wherein the copper species on the surface of activated carbon are Cu 0 Cu + and Cu 2+ The cerium species exist in mixed valence states, and are dispersed in the activated carbon channels as mixed oxides of CeO2 and Ce2O3.
[0016] Furthermore, the adsorbent has reversible regeneration capability. When the adsorption is saturated, the desorption process is as follows: by purging with inert gas or 5N grade high-purity nitrogen at 250-350℃ for 2-4 hours, more than 90% of the initial adsorption performance can be restored.
[0017] The regeneration method of the adsorbent of this invention utilizes an inert gas to purge at high temperature, thereby desorbing impurities adsorbed on the active sites and simultaneously resetting oxidized metal sites, thus realizing the recycling of the adsorbent.
[0018] Compared with the prior art, the present invention has the following advantages: The adsorbent of this invention can not only reduce CO2 in trifluoromethane to below 100 ppb and fluorocarbon compounds to below 0.05 ppm, but also achieve multiple regenerations through inert gas heating and purging. The adsorption capacity decay rate after regeneration is less than 5%, significantly reducing the production cost of electronic-grade trifluoromethane and the pressure of solid waste treatment. Specifically, this is reflected in the following points: 1. Deep removal capability: By constructing Cu + The -CeO2 active interface enables the chemical adsorption of CO2 and the catalytic cracking of fluorocarbons, and can stably control impurities at extremely low levels (CO2 < 100 ppb, fluorocarbons < 0.05 ppm).
[0019] 2. Recyclable: Breaking through the irreversible limitation of the original silver-zinc system, this adsorbent can be regenerated through simple thermal purging, and the number of regenerations can reach more than 10 times, which greatly reduces the unit consumption cost.
[0020] 3. Economic and environmentally friendly: It uses inexpensive metals such as copper and cerium to replace precious metals such as silver, and reduces the generation of solid waste, which meets the requirements of green chemical industry.
[0021] 4. High selectivity: The binding of the hydrophobic carrier to the CO2-loving active site ensures that the main component HFC-23 is not adsorbed in large quantities when it passes through, thus improving the product yield. Detailed Implementation
[0022] Example 1
[0023] 30-mesh hydrophobic coconut shell charcoal (specific surface area 1000 m²) was selected. 2 (g), boiled in 0.5 mol / L dilute hydrochloric acid for 1 h, washed with deionized water until neutral, and dried at 100 °C for 12 h.
[0024] Preparation of impregnation solution: Dissolve 30g copper nitrate and 60g cerium nitrate in 1L deionized water, add 15g citric acid, and stir for 30 minutes until clear.
[0025] Impregnation: Mix the pretreated activated carbon with the above impregnation solution at a volume ratio of 1:1, stir and impregnate at room temperature for 30 minutes, and let stand for 2 hours.
[0026] Drying and calcination: The sample was placed in a forced-air drying oven and dried at 120℃ for 4 hours. It was then transferred to a tube furnace, and a mixture of H2 and N2 (5% by volume) was introduced. The temperature was increased to 450℃ at 5℃ / min and calcined at this constant temperature for 3 hours. The calcined material was then purged with 5N high-purity nitrogen at 250℃ for 1.5 hours. After cooling to room temperature, adsorbent product A was obtained.
[0027] Example 2
[0028] 30-mesh hydrophobic coconut shell charcoal (specific surface area 1000 m²) was selected. 2 (g), boiled in 0.5 mol / L dilute hydrochloric acid for 1 h, washed with deionized water until neutral, and dried at 100 °C for 12 h.
[0029] Preparation of impregnation solution: Dissolve 30g copper nitrate and 60g cerium nitrate in 1L deionized water, add 15g citric acid, and stir for 30 minutes until clear.
[0030] Impregnation: Mix the pretreated activated carbon with the above impregnation solution at a volume ratio of 1:2, stir and impregnate at room temperature for 30 minutes, and let stand for 2 hours.
[0031] Drying and calcination: The sample was placed in a forced-air drying oven and dried at 120℃ for 4 hours. It was then transferred to a tube furnace, and a mixture of H2 and N2 (5% by volume) was introduced. The temperature was increased to 450℃ at 5℃ / min and calcined at this constant temperature for 3 hours. The calcined material was then purged with 5N high-purity nitrogen at 250℃ for 1.5 hours. After cooling to room temperature, the adsorbent product B was obtained.
[0032] Example 3
[0033] 30-mesh hydrophobic coconut shell charcoal (specific surface area 1000 m²) was selected. 2 (g), boiled in 0.5 mol / L dilute hydrochloric acid for 1 h, washed with deionized water until neutral, and dried at 100 °C for 12 h.
[0034] Preparation of impregnation solution: Dissolve 30g copper nitrate and 60g cerium nitrate in 1L deionized water, add 15g citric acid, and stir for 30 minutes until clear.
[0035] Impregnation: Mix the pretreated activated carbon with the above impregnation solution at a volume ratio of 1:3, stir and impregnate at room temperature for 30 minutes, and let stand for 2 hours.
[0036] Drying and calcination: The sample was placed in a forced-air drying oven and dried at 120℃ for 4 hours. It was then transferred to a tube furnace, and a mixture of H2 and N2 (5% by volume) was introduced. The temperature was increased to 450℃ at 5℃ / min, and calcined at this temperature for 3 hours. The calcined material was then purged with 5N high-purity nitrogen at 250℃ for 1.5 hours. After cooling to room temperature, the adsorbent product C was obtained.
[0037] Example 4
[0038] 20-mesh hydrophobic coconut shell charcoal (specific surface area 800 m²) was selected. 2 (g), boiled in 1 mol / L dilute hydrochloric acid for 2 h, washed with deionized water until neutral, and dried at 80 °C for 15 h.
[0039] Preparation of impregnation solution: Dissolve 60g of copper nitrate and 52g of cerium nitrate in 1L of deionized water, add 11.2g of citric acid, and stir for 10 minutes until clear.
[0040] Impregnation: Mix the pretreated activated carbon with the above impregnation solution at a volume ratio of 1:1, stir and impregnate at room temperature for 50 minutes, and let stand for 2 hours.
[0041] Drying and calcination: The sample was placed in a forced-air drying oven and dried at 140℃ for 2 hours. It was then transferred to a tube furnace, and a mixture of H2 and N2 (10% by volume) was introduced. The temperature was increased to 500℃ at 4℃ / min and calcined at this constant temperature for 2 hours. The calcined material was then purged with 5N high-purity nitrogen at 200℃ for 2 hours. After cooling to room temperature, the adsorbent product D was obtained.
[0042] Example 5
[0043] 40-mesh hydrophobic coconut shell charcoal (specific surface area 1200 m²) was selected. 2 (g), boiled in 0.8 mol / L dilute hydrochloric acid for 1.5 h, washed with deionized water until neutral, and dried at 120 °C for 10 h.
[0044] Preparation of impregnation solution: Dissolve 30g copper nitrate and 105g cerium nitrate in 1L deionized water, add 35g citric acid, and stir for 60min until clear.
[0045] Impregnation: Mix the pretreated activated carbon with the above impregnation solution at a volume ratio of 1:1, stir and impregnate at room temperature for 20 minutes, and let stand for 2 hours.
[0046] Drying and calcination: The sample was placed in a forced-air drying oven and dried at 100℃ for 6 hours. It was then transferred to a tube furnace, and a mixture of H2 and N2 (8% by volume) was introduced. The temperature was increased to 350℃ at 3℃ / min and calcined at this constant temperature for 5 hours. The calcined material was then purged with 5N high-purity nitrogen at 300℃ for 1 hour. After cooling to room temperature, the adsorbent product E was obtained.
[0047] Performance testing The adsorbents from Examples 1-5 were loaded into adsorption columns (DN32×400mm), and a feed gas of trifluoromethane (composition: CO2 1208.5ppm, CFC-13 0.508ppm, HCFC-22 537.57ppm, remainder CHF3) was introduced at a flow rate of 200ml / min. The impurity content of the outlet gas was detected, and the results are shown in the table below: Table 1. Impurity content of outlet gas
[0048] Regeneration performance test Example 1 was desorbed and regenerated using the saturated adsorbent: purged at 300°C for 3 hours under a 5N high-purity nitrogen atmosphere, and then the adsorption test was repeated after cooling.
[0049] • CO2 removal rate after the first regeneration: 99.1% (initially 99.3%); • CO2 removal rate after the 5th regeneration: 98.7%; • CO2 removal rate after the 10th regeneration: 96.5%.
[0050] Example 1 was desorbed and regenerated using the saturated adsorbent: purged at 350°C for 3 hours under a 5N high-purity nitrogen atmosphere, and then the adsorption test was repeated after cooling.
[0051] • CO2 removal rate after the first regeneration: 99.0% (initial 99.3%); • CO2 removal rate after the 5th regeneration: 98.5%; • CO2 removal rate after the 10th regeneration: 96.0%.
[0052] Example 1 was desorbed and regenerated using the saturated adsorbent: purged at 250°C for 3 hours under a 5N high-purity nitrogen atmosphere, and then the adsorption test was repeated after cooling.
[0053] • CO2 removal rate after the first regeneration: 98.7% (initially 99.3%); • CO2 removal rate after the 5th regeneration: 98.1%; • CO2 removal rate after the 10th regeneration: 95.6%.
[0054] Comparative Example 1 The silver-zinc modified activated carbon disclosed in Chinese patent CN114272893A was used as a control sample. Its preparation method is as follows: hydrophobic coconut shell carbon was boiled in 0.5mol / L HCl for 1h and then dried. It was then impregnated with silver nitrate and zinc chloride solution, stirred at room temperature for 30min and then dried in air without reduction calcination treatment.
[0055] The comparative sample was loaded into the same adsorption column and purged with the same feed gas (CO2 1208.5ppm, CFC-130.508ppm, HCFC-22 537.57ppm) to test its adsorption and regeneration performance.
[0056] In contrast, the adsorbent in Comparative Example 1 only achieved an activity recovery rate of 45% after trying the same regeneration conditions, demonstrating that the present invention has significant regeneration advantages.
[0057] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of protection of the present invention should be determined by the scope defined in the claims. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane, characterized in that: Includes the following steps: (1) Carrier pretreatment: Hydrophobic coconut shell activated carbon is acid washed and deashed, and then dried; (2) Preparation of impregnation solution: Dissolve soluble copper salt and soluble cerium salt in deionized water, add complexing agent citric acid, stir and mix evenly to obtain copper-cerium composite impregnation solution; (3) Impregnation: The hydrophobic coconut shell activated carbon after carrier pretreatment is immersed in the copper-cerium composite impregnation solution, stirred and impregnated, and then dried. (4) Reduction roasting: The dried material is placed in a mixed atmosphere containing hydrogen and roasted to obtain the adsorbent product.
2. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbons from trifluoromethane according to claim 1, characterized in that: In step (1), the hydrophobic coconut shell activated carbon has a particle size of 20-40 mesh and a specific surface area of 800-1200 m². 2 / g; The method for acid washing and deashing is as follows: boil in 0.5-1 mol / L dilute hydrochloric acid for 1-2 hours; The drying conditions are: 80-120℃ for 10-15 hours.
3. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane according to claim 1, characterized in that: In step (2), the soluble copper salt is copper nitrate, the soluble cerium salt is cerium nitrate, the molar ratio of copper to cerium is 1:(0.5-2), and the total metal ion concentration in the impregnation solution is 3-10wt%.
4. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbons from trifluoromethane according to claim 1, characterized in that: In step (2), the amount of citric acid added is 10%-30% of the total mass of copper salt and cerium salt; The mixing time is 10-60 minutes.
5. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane according to claim 1, characterized in that: In step (3), the volume ratio of the pretreated hydrophobic coconut shell activated carbon to the copper-cerium composite impregnation solution is 1:1-3. The stirring and soaking time is 20-50 minutes; The drying conditions are: 100-140℃ for 2-6 hours.
6. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane according to claim 1, characterized in that: In step (4), the hydrogen-containing mixed atmosphere is a mixture of hydrogen and nitrogen, wherein the volume percentage of hydrogen is 5%-10%, and the heating rate during the calcination process is 3-5℃ / min.
7. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane according to claim 1, characterized in that: In step (4), the roasting temperature is 350-500℃ and the time is 2-5h.
8. The method for preparing an adsorbent for removing trace amounts of carbon dioxide and fluorocarbon compounds from trifluoromethane according to claim 1, characterized in that: Step (4) is followed by an activation step, in which the calcined material is purged with high-purity nitrogen gas at 200-300°C for 1-2 hours. The purity of the high-purity nitrogen gas is 5N grade.
9. An adsorbent prepared by the method according to any one of claims 1 to 8, characterized in that: The adsorbent comprises copper species on the surface of activated carbon and cerium species dispersed within the pores of the activated carbon, wherein the copper species on the activated carbon surface are Cu. 0 Cu + and Cu 2+ The cerium species exist in mixed valence states, and are dispersed in the activated carbon channels as mixed oxides of CeO2 and Ce2O3.
10. The adsorbent according to claim 9, characterized in that: Once adsorption is saturated, the desorption process involves purging with inert gas or high-purity nitrogen at 250-350℃ for 2-4 hours to restore more than 90% of the initial adsorption performance.
Citation Information
Patent Citations
Preparation method of adsorbent for removing trace carbon dioxide and fluorocarbon in trifluoromethane
CN114272893A